THE IMPACT OF SCHOOL FEEDING PROGRAMMEME ON ENROLMENT IN PRIMARY SCHOOLS IN ARID AND SEMI-ARID AREAS. A CASE OF KATHONZWENI SUB-COUNTY, MAKUENI COUNTY, KENYA - James, Mbondo Kitaka; Kathuri, Prof. Nephat J.; Kibaara, Dr. Tarsilla. M. (IJRDO- Journal of Educational Research, 2017)
Providing school meals can play a critical role in ensuring that children learn well. Many childrenfrom poor homes go to school hungry. This leads to poor concentration in class. This study soughtto determine the impact of the School Feeding Programme (SFP) on enrolment in primaryschools in Arid and Semi-Arid Areas, taking a case of Kathonzweni Sub-County, MakueniCounty, Kenya. Based on the findings of the study, SFP had a high influence on enrolment ofchildren into primary schools in Kathonzweni Sub-County. The study established that SFPgreatly influenced school attendance by pupils in Kathonzweni Sub-County. They had asignificant effect on retention of pupils in the learning process. The study also revealed thatchallenges facing school heads in the course of implementing the school feeding programmeincluded: late funds disbursement, parent’s failure to pay funds to cater for the cook, water andfirewood shortage. It was therefore recommended that the financiers of the SFP should ensurethat enough funds were released in time to give schools’ management enough time to purchaseenough food stuffs in time.